Risk Assessment Providing Solid Grounds For Strategic Management In The Insurance Industry - Ljubomir Drakulevski; Tamara Kaftandzieva (European Scientific Journal, ESJ, 2021)
The insurance industry is undergoing more turbulence than any other industry since nowadays it is faced with a variety of strategic risks–emerging threats and challenges: change in regulation, customer behavior, distribution channels, competition, and new innovative technologies. The aim of this study is to propose strategic management directions towards risk assessment in the insurance companies, which could implicate the overall performance of many engaged in this sector. Given the growing importance of the insurance companies, profitability is considered as one of the key performance metrics which is under major influence of internal factors. This type of analysis is an important tool in determining the quick and decisive response of the managers to important new challenges and opportunities, especially in absence of a risk management regulatory framework. For this purpose, the data of 11 non – life insurance companies operating in North Macedonia from the period 2012 – 2019 is examined. The estimated model with random effects on panel data suggests a negative and significant influence of the loss ratio, the expense ratio, the retention rate, and the premium to surplus ratio on the profitability of non – life insurers, as measured by the return on assets (ROA), whereas the size has a positive impact on the profitability. The influence of remaining variables on the profitability was not found to be statistically significant. The obtained results were alighed in recommendations which can be used to potential future improvement and viable business strategies considering the specific and vulnerable Macedonian insurance context.